Pd–Ru Bimetallic Nanocrystals with a Porous Structure and Their Enhanced Catalytic Properties. (15th January 2018) - Wan, Shulin; Wang, Qingxiao; Ye, Haihang; Kim, Moon J.; Xia, Xiaohu
Abstract: This work, for the first time, reports the synthesis, characterization, and catalytic properties of a novel type of bimetallic nanocrystals—Pd–Ru nanocrystals with a highly porous structure on the surface. The synthesis relies on a seed‐mediated growth, at which Ru atoms are added to the surface of preformed Pd nanocubes as the seeds. The key to the successful synthesis is to direct the crystal growth along a 3D island mode through kinetic control. The Ru shells on Pd surfaces primarily take a hexagonal close packing (hcp) crystal structure. The extent of porosity for Ru shells can be conveniently controlled by adjusting the amount of Ru precursor introduced to a synthesis. The Pd–Ru porous nanocrystals exhibit a substantially enhanced peroxidase‐like activity with a catalytic constant ( K cat ) as high as 4.8 × 10 5 s −1, which is two‐orders‐of‐magnitude greater than the K cat value of natural peroxidases. Abstract : Palladium‐ruthenium core‐shell nanocrystals with a highly porous structure on the surface are synthesized and carefully characterized. The key to the porous structure formation is to direct the growth of Ru on Pd seeds along a 3D island mode. These bimetallic nanocrystals possess inherent peroxidase‐like properties, with a catalytic activity much higher than natural peroxidases.